Proximate Characteristics of Smoked Salted Mackarel Fish Products - Lekahena, Vanessa Natalie Jane (Agrikan: Jurnal Agribisnis Perikanan, 2020)
Salting and smoking fish is a traditional processing method that aims to preserve by adding salt, smoke and heat to the processed product, because it can reduce the moisture content of processed products that inhibit microbial growth so that it has a long shelf life with distinctive taste and aroma. This study aims to determine the proximate characteristics of smoked salted mackerel fish processed using different concentrations of salt solution, while the benefits can be used as input for the development of home industries and fisheries processing farmers in North Maluku. The results of this study stated that the increase the concentration of salt solution used for the process of immersion of fish before the drying and smoking processes affect the proximate characteristics of salted smoked  mackerel fish with moisture content value of 16.1099-22.7264%; ash 15.4686-18.9986%; fat 7.0559-9.6603%; and protein 47.3287-49.6388%, and carbohydrates 0.7752-15.4068%.